What interventions are required to reduce road traffic injuries in Africa ? : a scoping review of the literature - (:unkn) unknown (My University, 2018)
Road traffic accidents are the major cause of mortality among people aged 15-29 years in Africa. World Health Organisation (WHO) and the World Bank launched a Decade of Action for Road Safety in 2011 with the goal of halving the number of injuries and deaths on the roads. No progress has been reported in Low and Middle Income Countries (LMICs) and the number of deaths remains very high. To reach the target set, there is a need for interventions in several areas. This scoping review proposes to produce a synthesis by identifying the kinds of interventions and outcomes which have been carried out on the African continent. Using the scoping studies method, 23 articles were selected and analysed. The study shows that interventions were developed in four fields: road safety policy, health education, safety equipment and data collection. It shows also that there were records of interventions in only twelve countries, mostly in Eastern and Southern Africa. The main conclusion of this study reveals both a lack of road safety interventions and shortcomings in the assessment of those performed and selected for our study.
Keywords: African Research